Smart diagnosis algorithm of the open-circuit fault in a photovoltaic generator, ISBN: 978-1-4799-8212-7 - Wail Rezgui (CEIT, 2015 3rd International Conference on Control, Engineering & Information Technology, 2015)
This article proposed a new smart diagnosis algorithm of the open-circuit fault in a PV generator. For the faults conventional diagnosis, it used the analysis of the actual operation parameters of the PV generator. For the faults smart diagnosis, it based on the optimization of SVM technique by the neural network for the classification of observations located on its margin. The resulting algorithm can ensure a better monitoring function of the open-circuit fault within the PV generator, with a high classification rate and a low error rate.